Climate Change Impacts on Indonesian National Parks - Lambok P. Sagala (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2019)
Indonesia is the third largest tropical forest country. There are about 125 million Ha of total Indonesian forests, in which 27 million Ha are conservation areas. Besides conserving species and ecosystem, national parks are also natural solutions for climate change problem. Despite its vital roles in mitigating climate change, national parks are affected by climate change. Changing in climate alters forest composition and structure, scenic beauty, cultural heritage, biodiversity, and ecosystem services. These impacts eventually could harm tourism, and national park development. National park is an interesting landscape to study climate change. It is a nature conservation area, has native ecosystem, managed using zoning system and mainly used for research, education, and nature tourism. Many of the national parks are protected from urbanization, timber harvesting, grazing, and other non-climate factors. Therefore, it can be said that human is one of the main causes of climate change. Taking into account the nature of national parks and inevitable impact of climate change, research needs to be done to assess how climate change affects national parks. Using literature review, this paper will explore to what extent the research on impacts of climate change in Indonesia national parks has been done and provide information regarding existing mitigation and adaptation actions.